Electroporation of protoplasts - Bates, G.W.
A protocol is described for the delivery- of plasmid DNA into plant protoplasts by means of electroporation. Expression of the DNA is monitored 24 h later by a "transient assay" for chloramphenicol acetyltransferase (CATL Stable transformants are recovered by selecting for kanamycin resistance using a modified version of the agarose-bead technique.
Keywords: DIRECT GENE TRANSFER; STABLE TRANSFORMATION; DNA UPTAKE; TRANSIENT EXPRESSION; CAT EXPRESSION; KANAMYCIN RESISTANCE